Implementation of Multicultural Education in Islamic Education Subjects through Collaboration of Online Applications as Character Building - Andi Baso Malla, Hamlan; Almahdali, Ismail; Ratu, Bau; ., Misnah (KnE Social Sciences, 2023)
This research was motivated bymulticulturalism, namely people who have a background of differences in ethnicity, religion, ethnicity, culture and between groups. On the one hand, this diversity is the potential strength of a large and united nation state in building great peace and civilization, but on the other hand, the potential for conflicts to disrupt the stability of the nation and can hinder development and the existence of diversity on one side of this diversity is the starting point for disputes, vertical conflicts. and horizontally, a multidimensional crisis. The study of this paper focuses on multicultural education as learning material through a process of instructional activities in building multicultural awareness to develop the religious and social character of students at the Junior High School level in Palu City. The data collection techniques were carried out by observation, interview and documentation. The data was collected by triangulation to check the validity of the data in finding the validity of the data. Data were analyzed using data reduction, data display, and data verification. Research Results Description The application of students’ culture of tolerance has four factors that influence the occurrence of conflict in society, namely the influence of globalization from Western culture, economic factors, the existence of rich and poor groups, democratic behavior carried out freely without limits and the destruction of individual dignity, and will developed through animated games for students. Keywords: Character building; Islamic education; multicultural education